A NEW VERSION OF THE MAP OF RECENT VERTICAL CRUSTAL MOVEMENTS IN THE CARPATHO-BALKAN REGION BASED ON THE COLLOCATION METHOD - Nikonov A.A.; Skryl V.A.; Lisovets A.G. (My University, 1987)
The paper is concerned with the problem of adequate mapping of resulting discrete values of the movement velocity as a field. The authors used a statistical method (collocation) to represent measurement results for the Carpatho-Balkan region as a field of recent crustal movement velocity. The collocation method gives a possibility of avoiding a strong influence that the available geomorphological and geological knowledge of the area and individual notions of map-makers have on the drawing of isolines of velocity movements. The new version of the map of recent vertical movements in the Carpatho-Balkan region shows some notable differences from the 1979 version.